Pelatihan Pembuatan Gambar Teknis pada Proyek Konstruksi Sederhana pada Siswa Jurusan Desain Permodelan dan Informasi Bangunan di SMK Negeri 2 Dumai: Technical Drawing Making Training on Simple Construction Projects for Students of Department of Building Modeling and Information Design at SMK Negeri 2 Dumai - Aziz, Azwan; Srihandayani, Susy; Halimatusadiyah, Halimatusadiyah; Desriyati, Welly (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The ability to create high-quality, accurate working drawings is one of the most essential skills in industrial construction. Working drawings that do not meet standards can lead to errors in project implementation, increase costs, and extend project timelines. Currently, learning at SMK Negeri 2 Dumai focuses more on mastering design software, with insufficient emphasis on creating working and as-built drawings. As a result, students do not yet have adequate skills to develop complete technical documents that meet industry standards. The purpose of this activity is to help students and teachers clearly understand the activities to be carried out and to commit to actively participating in each stage of the program. The program implementation method includes five main stages: socialization, training, technology application, mentoring and evaluation, and program design. Each stage is carried out systematically to improve students' understanding and skills in creating plan drawings, working drawings, and as-built drawings. The results were obtained from 45 students who attended the entire session. Most students could correctly answer basic questions about the technical drawing document cycle. The accompanying teacher stated that the material had never been systematically presented in school before. This activity provides a strong conceptual understanding of the importance of technical drawings in construction projects. Students of SMK Negeri 2 Dumai can now identify the differences in the functions of each technical drawing and understand the roles of the parties involved in its preparation.